Polymer powder adhesion to metallic surface improvement with plasma - Hladík, J.; Píchal, J.; Špatenka, P. (Вопросы атомной науки и техники, 2008)
Useful method for corrosion prevention is coating of a base material with a suitable substance. It performs a barrier between the base material and its environment. Great attractions in this field have found polymers, among them polyethylenes (PE). Due to the low adhesion grade of unmodified polymer powder or granules the application of any modification process increasing the adhesion grade is crucial. At present there is no universal approach to polymer adhesion improvement and there have been employed various quite different techniques. Our research employed the PE adhesion improvement by plasma modification. There were used two plasma reactors – the microwave low pressure reactor and the atmospheric reactor employing dielectric barrier discharge (DBD). The adhesion of the powder was determined by measurement of strength force demanded for displacement of the PE-metal joint.